Identifikasi Koin Kuno Dinasti Song Koleksi Museum Situs Kotta Cina - Nicky Johanes Sitanggang; Dewi Ningsih Br Manalu; Lamsar Latinus Sihombing; Ichwan Azhari (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
The Kotta Cina Site Museum is a museum where the archaeological findings of The Kotta Cina are stored in Medan city precisely near the Siombak lake, Medan Marelan District. The ancient coins of Chinese character are a proof that the Chinese people had carried out trading activities in the Kotta Cina we know today. Some of the coins collected by the Kotta Cina Site Museum are ancient coins dating back to the Song Dynasty. This study aims to identify ancient coins of the Song Dynasty to find out the identity of the coins, the size of each coin, and the type of material used in making coins. The research method used is a qualitative descriptive method to describe, describe, explain, explain, and answer in more detail the problem under study. From the results of the research, of the many coins collected by the Kotta Cina Site Museum, there are 34 Song Dynasty coins consisting of 31 Northern Song Dynasty coins and 3 Southern Song Dynasty coins. The entire coin identified was made of the main material iron which had a size of ≤23.99 mm including small coins and a ≥ size of 24.00 mm including large coins.